(untitled) (Research, Society and Development, 2021)
Each dairy property is unique and has particularities in its structure and management practices. Therefore, implementing biosafety measures is a necessary challenge for dairy cattle farming, since there are many diseases arising from pathogen contamination that can be avoided if these measures are properly put into practice. Thus, to provide the consumer with insurance and quality, in addition to ensuring the safety of animals, employees and everyone involved in the production chain, it is essential to know the principles of biosecurity and manage them in the production system. It is up to the responsible professional to assess the risks or dangers involved in maintaining the health of the animals, and from this analysis, compose a biosecurity plan aimed at mitigating health damage to the herd. For this, it is necessary not only commitment and training through health education and preventive measures, but also adequate supervision to ensure its execution. Thus, it is possible to establish sustainable production systems, generating a higher rate of productivity for the producer, as a mutual component, the lowest number of losses in production and guaranteeing the consumer a safe and quality product.